The physiological and pathophysiological roles of platelet CLEC-2 - Navarro-Núñez, Leyre (2013)
CLEC-2 is a C-type lectin receptor which is highly expressed on platelets but also found at low levels on different immune cells. CLEC-2 elicits powerful platelet activation upon engagement by its endogenous ligand, the mucin-type glycoprotein podoplanin. Podoplanin is expressed in a variety of tissues including lymphatic endothelial cells, kidney podocytes, type I lung epithelial cells, lymph node stromal cells and the choroid plexus epithelium. Animal models have shown that the correct separation of the lymphatic and blood vasculatures during embryonic development is dependent on CLEC-2-mediated platelet activation. Additionally, podoplanin deficient mice show abnormalities in heart, lungs, and lymphoid tissues, whereas absence of CLEC-2 affects brain development. This review summarizes the current understanding of the molecular pathways regulating CLEC-2 and podoplanin function and suggests other physiological and pathological processes where this molecular interaction might exert crucial roles.